Pelatihan Menggunakan Kaki Bagian Dalam Pada Permainan Sepak Bola Untuk Siswa/I Madrasah Ibtidaiyah [MI] Mathlaul Anwar Pangkalan Kelas 1 Dan 2 - Nazwa Nurharistiana; Fauzi Faturohman; Dede Imtihanudin; Idris Supriadi (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The foot kick method is generally the inside leg kick technique used to provide short passing that suits them. the most dominant movement in running, the main goal is to score as many goals as possible towards the opponent's goal. The purpose of this study was to determine the effect of deep kick training on shooting accuracy in soccer matches. The research method used is a literature search covering several sources such as primary and secondary sources. With the results of research from various sources to be able to conclude that the method of practicing kicking the inside of the leg affects the accuracy of the shot. "There is an effect of training to kick the ball with the inside of the foot, which affects shooting accuracy in soccer matches, using this method of oblique training. Thus, it can be concluded that how to kick the inside of the leg has a significant effect on shooting accuracy in a soccer match